Description of two new species of Dima Charpentier, 1825 from China (Coleoptera: Elateridae: Dendrometrinae) - Ruan, Yongying; Kundrata, Robin; Sormova, Eliska; Qiu, Lu; Zhang, Mengna; Jiang, Shihong (Zootaxa, 2018)
Dima guizhouensis Ruan, Kundrata & Qiu sp. nov. and Dima xiaolongi Ruan, Kundrata & Qiu sp. nov. are described from Guizhou and Hunan Provinces in China, respectively. Both species are easily distinguishable from most of their congeners by having a strongly convex pronotum and relatively long elytra with carinate interstria VI. The only superficially similar species is D. tianmuensis Qiu & Kundrata in Qiu et al. (2018) from Zhejiang Province. Habitus and main diagnostic characters are figured for both new species, and their systematic placement is discussed. The discovery of these species brings the total number of Dima species in China to 13.